Investigating the Effect of Rotor Angle to Characteristic Amplitudo Vibration Shaft on Wind Turbine Horizontal Axis Testing - Sianipar, Aston (New Approaches in Engineering Research Vol. 4, 2021)
The vibrations that arise in the axis of the wind turbine is a phenomenon that results from the unstable wind velocity coming from the angle of the wind attacked by the blade of the wind turbine itself. The abundant energy such as wind and water has not been maximally utilized, therefore this study is planned to seek for increased efficiency. Vibration is widely used as a tool to analyze both machines with rotation and translational motion. Vibration is widely used as a tool to analyze both machines with rotation and translational motion. Knowledge of data and vibration will which is yielded of vital importance for the treatment of repair analysis and also. This understanding can assist technician to reduce the happening of downtime and can improve advantage either from facet of peroduksi and also from longer wind turbine age. Vibration arising out effect of style of siklik [pass/through] existing machine elements, where the elements is showing off each other one another and didesifikasienergi [pass/through] structure in the form of vibration. Influence of vibration is the happening of clunk, go down performance him and performa of wind turbine and also can destroy component at wind turbine especially at pad and axis. At this research of angle; corner variation of blade (sudu / wind turbine rotor) to axis and also variation of speed of incoming wind. With the variation of can perceive and known by behavior of vibration that happened by measuring with appliance mengunakan agree vibration of vibrometer VQ-400-A OMETRON which in circuit with U3-Lv labjak distribute to PC in the form of digital voltage to analogous voltage. This model measure vibration at direction of horizontal axis of the abscis or where laser focus at rotatory wind turbine axis. To present result of measurement used by labjak which in circuit to PC laptop. This research yield that For the speed of wind [among/between] 3 - 4,5 m / s having smallest deviation use angle; corner of blade 30o [so that/ to be] vibration that happened more minimum that is [among/between] 0,2353425 mm to 0,356839 mm. Pursuant to calculation of critical frequency happened if turbine rotation frequency come up with frequency 9,464226 Hz and at simulation use ANSYS sofware apply frequency 4,1854 Hz.